Peningkatan Kesabaran Melalui Terapi Sufistik Studi Kasus Di Upt Pelayanan Sosisal Bina Remaja Dinas Sosial Provinsi Jawa Timur - Hanif Meysita (Prodi Tasawuf dan Psikoterapi Fakultas Usluhuddin dan Dakwah IAIN Kediri, 2022)
Patience is an attitude that is not uncommon for humans to easily do and practice patience in their daily lives because it requires consistent practical patience. Therefore, patience is a form of worship in the form of mental strength and attitude to deal with various kinds of verbal and physical disturbances in order to achieve the original goal and find a solution. Patience is a difficult thing because it requires patience, and it is much more difficult to practice patience in everyday life because it requires consistent practical patience. In the hadith of the Prophet Muhammad, patience consists of three kinds, namely; Patience in carrying out obedience, patiently avoiding disobedience, and patient with trials. On the other hand, certain circles, such as the Sufis, consider the three levels in the hadith to be in order from highest to lowest. So, the hardest patience is being patient with obedience and then patiently avoiding disobedience. As for being patient with trials, it is the lowest patience, although this is relative and subjective based on the point of view of each individual. Therefore, a patient attitude that is easy to do and apply to oneself in everyday life often becomes a difficult behavior for teenagers if there is a lack of regulation of emotions and feelings. Lack of knowledge of spirituality makes teenagers at their age do not know how to regulate emotions and apply patience to themselves.